1988
DOI: 10.1017/s0890037x00032243
|View full text |Cite
|
Sign up to set email alerts
|

Rose Rosette Disease on Multiflora Rose (Rosa multiflora) in Indiana and Kentucky

Abstract: Multiflora roses showing symptoms of rose rosette were found in nine counties in southern Indiana and two counties in northern Kentucky. The eriophyid mite, Phyllocoptes fructiphilus Kiefer (Acari: Eriophyidae), implicated as the vector of the rose rosette agent, occurred on most symptomatic material. Another eriophyid mite, P. rosarum Liro, was found on symptomatic material collected in Kentucky. Transmission of the causal agent into multiflora rose by shield budding and by P. fructiphilus was successful. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…appears to be declining in the United States due to rose rosette disease (Hindal et al . ), which is caused by a native emaravirus (Di Bello et al . ).…”
Section: Viruses Can Reverse Invasion Fronts and Cause Population Colmentioning
confidence: 99%
See 1 more Smart Citation
“…appears to be declining in the United States due to rose rosette disease (Hindal et al . ), which is caused by a native emaravirus (Di Bello et al . ).…”
Section: Viruses Can Reverse Invasion Fronts and Cause Population Colmentioning
confidence: 99%
“…One example involves infection of an invasive exotic species by a naturally occurring virus: multiflora rose (Rosa multiflora Thunb.) appears to be declining in the United States due to rose rosette disease (Hindal et al 1988), which is caused by a native emaravirus (Di Bello et al 2015). The remaining data are confined to viruses studied either for their value to humans as biological control agents or for their ability to cause disease in crops and domestic animals.…”
Section: Pathogens From the Native Communitymentioning
confidence: 99%
“…A similar disease, the rose rosette, is endemic in most of the United States (Hindal et al 1988), which suggests a close association with environmental or climatic conditions. Epstein and Hill (1995) reported that in Iowa conditions rose rosette incidence increased more quickly in open, sunlit sides than in heavily tree-shaded areas, where many of the affected plants remained free of symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Rose is frequently attacked by phytoplasmas. Phytoplasma-like diseases on rose, which might be called rosette (Thomas and Scott, 1953), witchesÕ-broom, dieback, wilt or spring dwarf, were reported in Canada (Epstein and Hill, 1995), New Zealand (Fry and Hammett, 1971), USA (Slack et al, 1976;Hindal et al, 1988;Tipping and Sindermann, 2000), the Netherlands (Bos and Perquin, 1975), UK (Thomas, 1979), former Russia (Protsenko et al, 1972;Protsenko and Surgucheva, 1975) and Poland (Kaminska et al, 2001(Kaminska et al, , 2003. Kaminska et al (2001Kaminska et al ( , 2003 identified for the first time the association of phytoplasma with rose degeneration at molecular level and proved that isolate belongs to subgroup 16SrI-B of aster yellow group.…”
Section: Introductionmentioning
confidence: 99%